2020
DOI: 10.3177/jnsv.66.427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Grape Seed Extract Supplementation on Hemodynamics in Normal Body Weight and Obese Males

Abstract: Recently, it has been reported that dietary supplementation with grape seed extract (GSE) ameliorates endothelial function and increase nitric oxide (NO) bioavailability. Thus, we investigated if elevated blood pressure and aortic stiffness (AoS) characterized in obese individuals are attenuated following acute GSE supplementation. Twenty men (obese510; normal body weight (NBW)510) participated in this study. Systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…One potential explanation contributing to the depressed pressor response to SHE may be due to an improvement in endothelial function via increased production of NO (Kim et al, 2018). This phenomenon has been observed in in human normotensive and prehypertensives during dynamic exercise (Dillon et al, 2020;Shari et al, 2022). Collectively, ndings indicate that GSE supplementation can attenuate BP response to exercise via an increase in vascular conductance.…”
Section: Gse Supplementation During Static Exercisementioning
confidence: 68%
“…One potential explanation contributing to the depressed pressor response to SHE may be due to an improvement in endothelial function via increased production of NO (Kim et al, 2018). This phenomenon has been observed in in human normotensive and prehypertensives during dynamic exercise (Dillon et al, 2020;Shari et al, 2022). Collectively, ndings indicate that GSE supplementation can attenuate BP response to exercise via an increase in vascular conductance.…”
Section: Gse Supplementation During Static Exercisementioning
confidence: 68%
“…In contrast, an improvement of the vascular health index of heavy smokers after long-term GSE application was described by Weseler et al and suggested to be associated with the induced increase in endogenous antioxidative potential [194]. Furthermore, the overall cardiac output, assessed by impedance cardiography, was improved after the application of a single GSE dose in obese, but not in healthy, participants [202]. ↓ 24 h energy intake (only in subjects with ≥7.5 MJ/day) [197] RCTs are listed according to publication date, whereby 6 RCTs for each group, sorted for highest cohort size (n) of available studies, are provided.…”
Section: Vitis Viniferamentioning
confidence: 90%
“…Regarding the cardiac parameters, the available data obtained from respective RCTs reveal that the long-term GSE treatment of prehypertensive, mild hypertensive, and postmenopausal participants results in decreased systolic and, in some studies, diastolic blood pressure levels [191,[199][200][201]. In two further RCTs, improvements in blood pressure were even measured after a single GSE application in overweight and prehypertensive participants [202,203]. However, no influence of GSE treatment on blood pressure in hypercholesteremia and pre/stage-I hypertensive participants was reported by Ras et al or Preuss et al [196,204].…”
Section: Vitis Viniferamentioning
confidence: 99%
“…Many clinical studies have evaluated the cardioprotective activity of grape. A randomized, double-blind, crossover test revealed that acute grape seed extract supplementation significantly reduced SBP and mean arterial pressure (MAP) in both normal-body-weight males (SBP: 103 ± 4 vs. 99 ± 3 mmHg; MAP: 75 ± 2 vs. 72 ± 2 mmHg) and obese males (SBP: 118 ± 3 vs. 112 ± 5 mmHg; MAP: 86 ± 3 vs. 84 ± 3 mmHg), and the effect in obese males might be associated with a reduction in cardiac output [ 64 ]. However, a systematic review and meta-analysis involving 19 trials based on healthy or unhealthy adults revealed that although grape seed extract supplementation significantly reduced DBP (−2.20 mmHg, 95% confidence interval (CI): −3.79 to −0.60) and heart rate (−1.25 bpm, 95% CI: −2.32 to −0.19), it had no significant effects on flow-mediated dilation (1.02%, 95% CI: −0.62 to 2.66) and SBP (−3.55 mmHg, 95% CI: −7.59 to 0.49) [ 65 ].…”
Section: Health Benefits Of Grapementioning
confidence: 99%